The Impact of Broadband Access on GDP per Capita : The Case of OECD Countries - Bagheri, Mohammad; Rodrigues, Ricardo Gouveia (Indian Journal of Marketing, 2017)
This paper investigated the possible relationship between the access of broadband and GDP per capita in 34 OECD countries for a 5-year period between 2009 to 2014. The data was collected from OECD's website as of April 2016. The relationship between broadband access and economic outputs at the macro-economic level was studied to add more knowledge and empirical evidence to the broadband studies, which have been conducted only on historical data. Correlation and regression analysis were conducted on the data to explore the relations and impact of fixed broadband and wireless mobile broadband subscriptions on the GDP per capita in the seven allocated regions of the OECD countries. The findings confirmed that broadband penetration contributed to the growth of GDP per capita in some regions, while it had a negative impact on others, which was in line with some of the earlier literature. The results revealed a better understanding of the differences in behavioral pattern of each region regarding the broadband access that had a strong negative impact on some of the developing countries' GDP such as region three and five (East Europe and Middle East), while other developed countries like region four (West Europe) did not demonstrate the growth of GDP by the contribution of broadband. Finally, we recommended using a disaggregated dataset for future research to get more insights.